A sustainable future for mining by 2030? Insights from an expert focus group. Issue 4 (November 2019) - Littleboy, Anna; Keenan, Julia; Ordens, Carlos M.; Shaw, Andrea; Tang, Roger H.; Verrier, Brunilde; Vivoda, Vlado; Yahyaei, Mohsen; Hodge, R. Anthony
Highlights: A multi-disciplinary expert group explored and synthesized the societal challenges facing mining in the 21 st century. A vision of the "ideal" mine of 2030 is presented and compared to expectations under "business as usual". Promoting trust between stakeholders is the key to a more equitable future. Solutions to strengthen the industry's contribution to the SDGs are discussed. Abstract: "What do you think the Mine of 2030 will be like?" Animated by this question, The University of Queensland's Sustainable Minerals Institute 2018 Master Class on "Mining and Society in the 21 st Century" developed a vision of an ideal future for the mining industry in 2030. Discussions explored the means to accelerate the industry's current trajectory towards greater sustainability. The class included doctoral students and academic researchers from diverse cultural backgrounds whose mining-focused work spans a broad range of disciplines. This paper distils the outcomes of the discussions and propose actions into a framework that centres on the interface between mining companies, governments and host communities. We argue that there are several concrete actions that the mining industry should adopt immediately to promote trust between stakeholders and strengthen the industry's contribution to achieving the United Nations Sustainable Development Goals.